3차원 프린터 응용을 위한 CT/MRI-영상 기반 GUI소프트웨어 개발 - 정영진(Young-Jin Jung) (방사선기술과학, 2018)
During last a decade, there has been increased demand for 3D-printed medical devices with significant improvement of 3D-Printer (also known as Additive. Manufacturing AM), which depend upon human body features. Especially, demand for personalized medical material is highly growing with being super-aged society. In this study, 3D-reconstructed 3D mesh image from CT/MRI-images is demonstrated to analyse each patients' personalized anatomical features by using in house, then to be able to manufacture its counterpart. Developed software is distributed free of charge, letting various researcher identify biological feature for each areas.